Adolescentes infractores: Análisis sobre su juzgamiento en delitos de asesinato y tráfico ilícito de sustancias catalogadas sujetas a fiscalización - Briones Chávez, Paula Alejandra (2025)
This research project covers relevant information regarding the prosecution of juvenile offenders in the country. The Ecuadorian State, in accordance with its current regulations, establishes that any individual between the ages of 12 and 18 is considered an adolescent. Additionally, the Constitution recognizes the rights of adolescents from the moment of conception, ensuring their protection under the principle of the Best Interests of the Child. By virtue of their status, children and adolescents enjoy immunity from criminal liability concerning the commission of offenses. However, if they do engage in such acts, they will be prosecuted within a Specialized Justice System governed by the Code of Childhood and Adolescence.